2018
DOI: 10.1021/acs.est.8b00104
|View full text |Cite
|
Sign up to set email alerts
|

A Flow Adsorption Microcalorimetry-Logistic Modeling Approach for Assessing Heterogeneity of Brønsted-Type Surfaces: Application to Pyrogenic Organic Materials

Abstract: Biogeochemical functioning of oxides and pyrogenic organic matter ( pyOM) are greatly influenced by surface and deprotonation characteristics. We present an energetics-based, logistic modeling approach for quantifying surface homogeneity (ϕ) and surface acidity ( pK ) for Brønsted-type surfaces. The ϕ, pK and associated deprotonation behavior of pyOM were quantified across feedstock (honey mesquite, HM; pine, PI; cord grass, CG) and heat-treatment-temperatures (HTT; 200-650 °C). At HTT200, lower ϕ [HM (0.86) >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…T he distinct physical, chemical, and surface properties of biochar as a matrix have to be considered in understanding and assessing its nutrient value (Farrell et al, 2013; Shepherd et al, 2017; Harvey et al, 2018). The typical high porosity (e.g., 62.5–85.1%; Gray et al, 2014) and high pH of biochar (e.g., pH 7–11; Qambrani et al, 2017) means that extraction methods optimized for soil are not necessarily appropriate for biochar.…”
mentioning
confidence: 99%
“…T he distinct physical, chemical, and surface properties of biochar as a matrix have to be considered in understanding and assessing its nutrient value (Farrell et al, 2013; Shepherd et al, 2017; Harvey et al, 2018). The typical high porosity (e.g., 62.5–85.1%; Gray et al, 2014) and high pH of biochar (e.g., pH 7–11; Qambrani et al, 2017) means that extraction methods optimized for soil are not necessarily appropriate for biochar.…”
mentioning
confidence: 99%
“…To the best of our knowledge, the apparent heterocyclic ring-opening mechanism reflected in HM400-derived (vs HM25-derived) w DOM (or its impact on reactivity) has never been reported in previous w DOM studies. However, there is precedence from charcoal studies that point to very different behaviors for leguminous and/or nitrogen-rich feedstocks (like HM) compared to their nonleguminous and/or nitrogen-deficient counterparts. , For instance, Knicker et al found that while charcoals from nonleguminous and/or nitrogen-deficient feedstocks tended toward increased levels of aromatic condensation, higher alkyl C contents are typical of charcoals from leguminous and/or nitrogen-rich feedstocks. Knicker et al further noted that this higher alkyl C content in charcoals from leguminous and/or nitrogen-rich feedstocks would render them more susceptible to biological or chemical oxidation and subsequently dissolution than would be commonly assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Knicker et al 35 further noted that this higher alkyl C content in charcoals from leguminous and/ or nitrogen-rich feedstocks would render them more susceptible to biological or chemical oxidation and subsequently dissolution than would be commonly assumed. Harvey et al 34 found that while the diversity in R groups attached to the carboxyl decreased in grass charcoals at HTTs between 350 and 650 °C, that in HM charcoals increased over the same HTT range. The difference in the trajectory of R group diversity with charring was attributed to HTT-promoted condensation of the soft tissue-dominated grass feedstock compared to HTT-promoted disintegration of the more thermally resistant, nitrogen-rich HM feedstock.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Scanning electron microscope images showed that ferrihydrite grains had an average size of 186 ± 86 μm (Figure S2). The surface charge of ferrihydrite was assessed using the ion-probe flow adsorption microcalorimetry method of Harvey et al 25 Probing experiments were conducted at pH 4, 5, 6, 7, 9, and 10 using K + and Na + as the cationic probes, whereas the anionic probes were Cl − and NO 3 − (Figure S3). Flow Adsorption Microcalorimetry Experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The similarity in the energetics between Cl/NO 3 (+3.15 J g −1 ) and NO 3 /Cl (−3.10 J g −1 ) is congruent with flow adsorption microcalorimetry studies of simple ion exchange reactions, which are completely reversible and occur via outer-sphere electrostatic interactions of anions (or cations) with metal oxides 23,27 and other charged surfaces. 21,25 The endothermic response of Cl/NO 3 relative to the exothermic response of NO 3 /Cl is reflective of the smaller ionic radius of Cl. 21,28 The unimodal shape and comparable reaction duration (30−35 min) of the Cl/NO 3 and NO 3 /Cl thermograms are also consistent with the simple reaction dynamics of outer-sphere ion exchange.…”
Section: ■ Introductionmentioning
confidence: 99%